Analysis of the Test Methods for High Modulus Fibers and Composites 1973
DOI: 10.1520/stp36485s
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Specimen Geometry on the Strength of Composite Materials

Abstract: This paper demonstrates the statistical relationships which exist between test specimens of different designs and how these relationships can be utilized in strength predictions. The specimens selected were the straight-sided tension coupon, uniaxial sandwich beam, and the acceptance-type flexure coupons. Experimental data were obtained for the [0]c, [90]c, [02/±45]c, [±45/902]c, and [0/±45/90]c laminates fabricated from Narmco 5505 boron-epoxy at various temperatures ranging from -65 to 420 F.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Previous research, [1][2][3][4][5][6][7], has shown that the strength and stiffness of fiber reinforced composite materials depend upon the size of the composite laminates. It has been demonstrated that the degree of influence depends upon the type of scaling level used, the stacking sequence, and the mode of loading.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research, [1][2][3][4][5][6][7], has shown that the strength and stiffness of fiber reinforced composite materials depend upon the size of the composite laminates. It has been demonstrated that the degree of influence depends upon the type of scaling level used, the stacking sequence, and the mode of loading.…”
Section: Introductionmentioning
confidence: 99%
“…For geometrically similar brittle materials, Eq.l may be written as: (2) where the shape parameter m is a constant for a given material. Thus, if m can be evaluated from two small size specimens, the strength of geometrically similar large size components can be predicted.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the strength decreased as the size of the FRP composite increased. However, this generality depended on the arrangement of fibers in the composite and the results were not always consistent [38][39][40][41]. This result was also obtained with FRP composite materials consisting of steel and GFRP panels.…”
Section: Test Results Under Accelerated Environmental Conditionsmentioning
confidence: 91%
“…The reasons for such a scatter are numerous, the main one being that the material is not homogeneous, with local variations in fibre content, orientation, hollows and resin-rich zones S00697 ᭧ IMechE 1998 JOURNAL OF STRAIN ANALYSIS VOL 33 NO 3 The MS was received on 6 March 1997 and was accepted after revision for publication on 17 April 1998. [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The fabrication processes and quality controls also have an influence [4]. In a general way, scatter is greater in these materials than in metals [5,6]. For all these reasons, in the present work a great number of static tests were performed and the cumulative distribution function (CDF) that best fitted the experimental results was used to determine the mechanical properties of GFRP studied under static load conditions.…”
Section: Introductionmentioning
confidence: 99%